Ageing management and monitoring of critical equipment at Seveso sites: An ontological approach. (July 2020) - Bragatto, Paolo A.; Ansaldi, Silvia M.; Agnello, Patrizia; Di Condina, Tiziano; Zanzotto, Fabio M.; Milazzo, Maria Francesca
Abstract: A safe "ageing" of Seveso establishments is a challenge for both operators and regulators. To this scope, Seveso III Directive required to integrate the equipment integrity issue into the safety management system for the major accident prevention; at the same time, the Italian Authority adopted a short-cut method for a quick ageing evaluation, which awards the application of the best techniques to control integrity and prevent deterioration-related failures. In this paper, the use of the ontology has been proposed to support decision-making about the implementation of technical solutions to control equipment ageing and comply the requirements of the Seveso legislation. To contrast deterioration mechanisms, the rapid development of data intensive smart sensors should be exploited and, in this frame, the automated on-line direct monitoring of equipment conditions, based on innovative low-cost sensors, is a novelty and promising solution. The developed ontology-based system points towards the adoption, when possible, of on-line monitoring. This solution provides much more data than traditional measurements and it is essential for the operators to understand how to merge concurrent information and data and to adequately control equipment deterioration. The ontology-based approach appears a viable solution even for this purpose. To demonstrate its potentiality, a real use-case has been used, where the model has been tested in finding the best technical solutions to improve the ageing management of an atmospheric distillation unit of a refinery in order to comply with safety requirements. A further use-case is given to show how the model can be used to react, after real-time damage signals, to restore safety conditions by means of an adequate decision-making. Graphical abstract: Image 1 Highlights: At Seveso sites, different technical and organizational factors contribute to control ageing and prevent major accidents. Ontology is invaluable to decide the best techniques to control equipment deterioration and meet Seveso requirements. Through the Ontology, data gathered by the innovative monitoring systems may effectively contribute to control ageing.